Aesculapius et hygia als Dii Maiores? - Hainzmann, Manfred (Studia Europaea Gnesnensia, 2017)
In an article published 1997 Géza Alföldy explained his ideas about the generic terms of dii Maiores and dii Magni. For the former term there are still no testimonies with theonymic referents known. This is not the case for the so called „Great Gods”. Exploring all epigraphic evidence including the epithets dominus et domina and other votive formulars, we come to the following conclusions: the dii Maiores rather do not refer to the main roman gods and goddesses but to the classical healers Aesculapius et Hygia. Like other Greek and Roman divinities they were together also invoked as dii Magni. It seems very likely, that the votive incriptions from Gorsium (dii Magni), which G. Alföldy was talking about, can also be linked with this famous couple of healing gods.